Development of data optimization methodology for non-destructive testing of concrete strength by the parameters of the electric response to impact excitation; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Fursa T. V. Tatyana Viktorovna (2016, 2016)
Title screen